PENGARUH PELATIHAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN PRODUKTIVITAS KERJA SEBAGAI VARIABEL MODERATING : (Studi pada PT. UNITED TRACTORS PANDU ENGINEERING) - Adawiah, Sarifah Robbiatul; Silalahi, Edward Efendi (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to determine and analyze how the influence of Training (X1), Motivation (X2) and Work Environment (X3) on Employee Performance (Y) with Work Productivity (Y) as a Moderating variable in the company PT United Tractors Pandu Engineering. The analysis used in this study includes checking validity and reliability (confirmatory factir analysis), testing measurement models between variables (path analysis), and structural model analysis. The effect of training on employee performance with a coefficient value of 0.288 p value 0.000 < 0.05. Furthermore, the results of the study also showed that motivation did not have a significant effect on employee performance with a coefficient value of -0.018 p value 0.399 < 0.05. Furthermore, the results showed a positive influence on employee performance with a coefficient value of 0.155 p value 0.011 >0.05. Furthermore, the training results also showed that the variable of work productivity did not moderate the influence of motivation on employee performance with a coefficient value of -0.131 p value 0.054 < 0.05. Then the results of work productivity research that moderated the effect of motivation on employee performance were not proven to moderate with a coefficient value of 0.138 p value 0.093 > 0.05. Furthermore, the results of work productivity research that moderates the influence of the Work Environment on employee performance are not proven to moderate with a coefficient value of -0.027 p value 0.388 >0.05. The results showed that training and motivation had a positive effect on employee performance, but training, motivation and work environment when moderated by work productivity had no effect. This shows that companies should pay more attention to forms of training, motivation and work environments that can support work productivity and improve employee performance.